Preparation method and separation application of surface post-crosslinked molecularly imprinted polymer

By combining the Marangoni effect and surface post-crosslinking imprinting technology, a surface post-crosslinking imprinted polymer based on wrinkled nano-silica was prepared, which solved the interfacial instability and specific surface area limitation in the dA separation process and achieved efficient and selective dA adsorption and separation.

CN121669189APending Publication Date: 2026-03-17JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511991584.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing surface imprinting technologies suffer from free radical side reactions and interfacial instability during dA separation, resulting in low recognition and separation efficiency. Furthermore, traditional imprinting materials have limited specific surface area, making it difficult to maintain high recognition activity in complex matrices.

Method used

By combining the Marangoni effect-driven adhesion strategy with surface post-crosslinking imprinting technology, a multifunctional copolymer was prepared on a wrinkled nano-silica substrate. The dopamine adhesion properties were utilized to establish stable interfacial connections, thereby preparing a surface post-crosslinking imprinted polymer, which enhances interfacial stability and recognition performance.

Benefits of technology

It achieves efficient adsorption and separation of dA, with high capacity, excellent selectivity and environmental adaptability, significantly improving the adsorption capacity and recognition efficiency of dA, and solving the interfacial instability and specific surface area limitation of traditional imprinting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669189A_ABST
    Figure CN121669189A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of molecular identification, adsorption and separation functional materials, and discloses a preparation method and separation application of a surface post-crosslinked molecularly imprinted polymer. According to the invention, an adhesion strategy and a surface post-crosslinking imprinting technology are combined to realize rapid and specific separation of 2 '-deoxyadenosine dA, and finally, a novel synthesis scheme related to preparation of functional copolymer modified wrinkle structure nano-silica WSNs is used to construct a surface post-crosslinking imprinting polymer WSNs (at) SPMIPs on WSNs. The method comprises the following steps: firstly, preparing WSNs of radial branches through a progressive seed growth mechanism; secondly, synthesizing a functional copolymer CP through free radical copolymerization; and then, pre-assembling the template molecule dA and the affinity monomer group in the CP, carrying out irradiation induction under ultraviolet light, carrying out post-crosslinking polymerization, and eluting the template to obtain the post-crosslinking imprinted polymer PMIPs. DA (Dopamine) is deposited on the WSNs under the mediation of DMSO (Dimethylsulfoxide); and finally, PMIPs are grafted on the surfaces of the WSNs, so that the adsorbent WSNs (at) SPMIPs is finally prepared and is used for the adsorption separation research of dA.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of preparation of molecular recognition adsorption separation functional materials, and particularly relates to a preparation method of surface post-crosslinking molecular imprinting polymer and separation application thereof. BACKGROUND

[0002] 2'-deoxyadenosine (dA) as an important purine nucleoside analogue is a key pharmaceutical intermediate for the construction of nucleoside analogue drugs against HIV and HBV infection, and shows a wide biomedical application prospect in the fields of antiviral, genetic engineering and pharmacological activity research. At present, in the research process of dA, due to the structural homology with other nucleosides and their derivatives, especially the interference of similar structure components in complex biological matrix, there is still a great challenge for the development of high recognition separation technology. Surface imprinting technology (SIT) exhibits unique advantages in adsorption separation through its template-specific molecular recognition mechanism, and the ordered binding cavities on the material surface ensure high recognition activity of the target analyte even in complex matrix. Compared with traditional imprinting methods, the surface-exposed imprinting sites enhance the mass transfer kinetics and significantly improve the adsorption / desorption efficiency. However, the research on dA recognition and separation reveals the key limitations in the free radical polymerization process: the generated free radicals will react with hydroxyl and amino groups, thereby damaging the structural integrity of dA-functional monomer assembly. At the same time, the elevated temperature conditions will exacerbate the solvent interference and multimonomer competitive coordination in the assembly process, ultimately leading to spatial mismatch of the molecular imprinting structure and producing defective recognition sites. This mechanism highlights the urgent need to develop alternative imprinting methods to inhibit non-specific interactions while maintaining molecular recognition fidelity, thereby achieving efficient dA separation through optimized imprinting strategies.

[0003] Surface post-crosslinking imprinting technology (SPIT) as an advanced functional material preparation strategy derived from SIT, its core mechanism involves replacing traditional functional monomers with multifunctional copolymers, and combining step-by-step polymerization and controllable crosslinking strategies to achieve precise construction and stability enhancement of recognition sites. However, the adsorbents prepared by copolymers mainly present solid core morphology, with limited specific surface area and pore structure, thereby limiting their practical application. This limitation highlights the urgent need to develop a substrate compatible with the SPIT framework and with high specific surface area. As a new type of biomimetic nanomaterial, wrinkled structure nanosilica (WSNs) overcomes the structural limitations of traditional silica-based adsorbents through its periodic three-dimensional corrugated topological structure, in which the hierarchical micro / nano-scale wrinkle design synergistically amplifies the surface area and active site density. However, the combination of SPIT and WSNs has not been explored, therefore it is urgent to develop effective strategies to establish stable interfacial connection between SPIT-derived imprinting layer and WSNs substrate.

[0004] In nature, marine mussels achieve firm adhesion in wet, salty and even hydrodynamic environments by using byssal thread proteins, and dopamine (DA) has become a key focus of biomimetic adhesion research due to its striking structural homology with mussel adhesive proteins. Therefore, the use of the adhesion properties of dopamine provides a promising strategy for establishing stable interfacial connections between SPIT-derived imprint layers and WSNs substrates. However, extensive studies on the adhesion mechanism show that when DA is applied to superhydrophilic substrates, the adhesion performance often becomes unstable or even fails, and the key failure mechanism is mainly attributed to the presence of an interfacial water layer. In order to circumvent this limitation, marine organisms such as barnacles have evolved an adaptive strategy that secretes lipid-rich substances before bonding to replace the interfacial water film through the Marangoni effect, which is a strategy that moves mass due to the presence of a tension gradient between two liquid interfaces with different surface tensions. Inspired by nature, the present strategy strategically selects a solvent system as a dispersion medium and combines the use of the Marangoni effect of the solid-liquid-liquid interface to actively remove the interfacial water layer, which can achieve stable dopamine adhesion on WSNs substrates, and ultimately prepare surface post-crosslinked imprint polymers (SPMIPs) with high molecular recognition performance and structural durability. This work combines WSNs, adhesion engineering strategies and SPIT, and the resulting SPMIPs exhibit enhanced interfacial stability, while establishing an innovative system that provides a comprehensive solution for dA adsorption separation technology with high capacity, excellent selectivity and environmental adaptability, etc. There is no related report so far. SUMMARY

[0005] In view of the deficiencies of the prior art, in order to solve the technical bottlenecks that the copolymer is difficult to achieve efficient adhesion on hydrophilic surfaces and the molecules with hydroxyl and amino groups are prone to side reactions under polymerization conditions, a preparation method of high-efficiency adhesion engineering strategy and controllable polymerization process is proposed, and is used for precise separation of dA.

[0006] In summary, the present application strategically combines the Marangoni effect-driven adhesion strategy with SPIT to achieve fast and specific dA separation, and finally constructs SPMIPs stably on the substrate through a new synthetic scheme involving amidization grafting to prepare multifunctional group modified WSNs. Firstly, the radially branched WSNs are prepared by the progressive seed growth mechanism in the emulsion system; secondly, the functional copolymer (CP, MAA-VBT-CEMA) is synthesized by free radical copolymerization of methacrylic acid (MAA), 1-(vinylbenzyl)thymine (VBT) and cinnamoyloxyethyl methacrylate (CEMA) dissolved in tetrahydrofuran (THF) solution under heating and stirring; then, under mild conditions, the template molecule dA is pre-assembled with the affinity monomer group in CP through complementary hydrogen bonding, and after cross-linking polymerization induced by ultraviolet light irradiation, the post-cross-linking imprinted polymer (PMIPs) is obtained after template elution; thereafter, under the condition of dimethyl sulfoxide (DMSO) mediation, DA is uniformly deposited on the WSNs, and then the PMIPs are stably amidized grafted to the surface of the WSNs to finally prepare the surface post-cross-linking imprinted polymer based on WSNs (WSNs@SPMIPs), and used for the adsorption and separation of dA.

[0007] The present application provides a preparation method of surface post-cross-linking imprinted polymer, and a simulated solution of dA is configured to evaluate the performance of the WSNs@SPMIPs adsorbent in selective adsorption and separation of dA. The method comprises the following steps: (1) Preparation of functional copolymer CP: The grafting monomer methacrylic acid MAA, the functional monomer 1-(vinylbenzyl)thymine VBT, the post-cross-linking monomer cinnamoyloxyethyl methacrylate CEMA and the photoinitiator azobisisobutyronitrile AIBN are dissolved in THF solution in proportion, and after nitrogen deoxygenation, stirring is carried out in an oil bath environment at 65℃ for a certain time, and after cooling to room temperature, it is precipitated and collected with n-hexane, and vacuum dried at 50℃ for 48 h to obtain MAA-VBT-CEMA, i.e. the functional copolymer CP.

[0008] (2) Preparation of PMIPs: The functional copolymer CP prepared in step (1) is pre-assembled with the template molecule 2'-deoxyadenosine dA in dichloromethane DCM; then the complex is dispersed in a quartz reactor, and photo-crosslinking and solvent evaporation are carried out under ultraviolet irradiation of a certain wavelength, after reaction, the unreacted CP is removed by washing with DCM, and finally the template molecule is eluted with a methanol / acetic acid (9:1, v / v) solution to obtain the post-cross-linking imprinted polymer material PMIPs.

[0009] Meanwhile, for comparison, the present application also prepared the post-crosslinking non-imprinted polymer material PNIPs, the synthesis steps are basically the same as above, only without adding the template molecule dA.

[0010] (3) Preparation of the wrinkled structure nanosilica WSNs: CTAB and n-butanol were dissolved in the aqueous urea solution, cyclohexane was added to the uniform mixture, TEOS was added dropwise under continuous mechanical stirring, the stirring was continued at room temperature, and the first heat treatment was carried out, the obtained product was washed with acetone and ethanol respectively, then dispersed in ethanol, hydrochloric acid was added for the second heat treatment, and WSNs were obtained after ethanol washing.

[0011] (4) Preparation of WSNs@DA: WSNs prepared in step (3) were dispersed in a Tris buffer solution (10 mM, pH 8.5 was adjusted by KOH), which contained a certain amount of DA; then, a certain amount of DMSO was added, the interfacial water layer on the surface of WSNs was dynamically replaced by the interfacial tension gradient driven by the Marangoni effect, and then continuous stirring was carried out at room temperature for a certain time; the composite material was washed with deionized water and ethanol, and finally vacuum dried to obtain DA functionalized WSNs with uniform surface coverage, namely WSNs@DA.

[0012] (5) Preparation of WSNs@SPMIPs: PMIPs prepared in step (2), hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) were activated in DMSO, then WSNs@DA prepared in step (4) was added, and continuous stirring was carried out at room temperature for a certain time, the obtained hybrid material was separated by centrifugation, and then washed with DMSO / ethanol and vacuum dried to obtain WSNs-based surface post-crosslinking molecularly imprinted polymer WSNs@SPMIPs.

[0013] For comparison, the present application also prepared WSNs-based surface post-crosslinking imprinted adsorbent (WSNs@SPNIPs), the synthesis steps are the same as above, only without adding the template molecule dA in the preparation process.

[0014] In step (1), the mass ratio of MAA, VBT, CEMA and AIBN is 1 mg: (1.5-2.5) mg: (4-8) mg: (0.14-0.2) mg.

[0015] In step (1), the stirring time in the oil bath environment is 12-24 h.

[0016] In step (2), the mass ratio of the functional copolymer CP and the template molecule dA is 1 mg:(0.1-0.15) mg.

[0017] In step (2), the pre-assembly time is 1.5-2.5 h.

[0018] In step (2), the wavelength of the ultraviolet lamp is 254 nm-390 nm, and the reaction time under ultraviolet light is 12 h.

[0019] In step (3), The mass ratio of CTAB, n-butanol and TEOS is 1 mg:0.8-1.2 mg:0.8-1.2 mg.

[0020] The mass ratio of CTAB, urea aqueous solution and cyclohexane is 500 mg:7.5 mL:7.5-12.5 mL, wherein the concentration of the urea aqueous solution is 0.4 M.

[0021] The concentration of hydrochloric acid is 12 M. The temperature of the first heat treatment is 70 DEG C, and the time is 20 h; the temperature of the second heat treatment is 70 DEG C, and the time is 12 h. In step (4), the mass ratio of the WSNs and the DA is 1 mg:(1-3) mg. The mass ratio of the WSNs, the Tris buffer solution and the DMSO is 50 mg:(10-30) mL:(0.75-2.25) mL.

[0022] In step (4), the stirring time is 18-30 h.

[0023] In step (5), the mass ratio of the WSNs@DA, the NHS, the EDC and the PMIPs is 1 mg:(1-2) mg:(1-2) mg:(1-3) mg.

[0024] In step (5), the activation time is 5 min, and the stirring time is 6-18 h.

[0025] The use of the WSNs@SPMIPs prepared in the application for selective adsorption and separation of dA.

[0026] Compared with the prior art, the beneficial effects of the application are as follows: The application combines the adhesion strategy driven by the Marangoni effect and the surface post-crosslinking imprinting technology to prepare a surface post-crosslinking imprinting polymer based on WSNs, regulates the imprinting recognition site by strengthening the interface stability and protecting the assembly and polymerization environment between the template molecules and the functional monomers, and the prepared surface post-crosslinking imprinting polymer adsorbent has high adsorption capacity, excellent selectivity and environmental adaptability for the target dA. Attached Figure Description

[0027] Figure 1 The NMR spectrum (a) and molecular weight curve (b) of the CP prepared in Example 1 are shown.

[0028] Figure 2 The images shown are scanning electron microscope (a1) and transmission electron microscope (a2-a3) images of the WSNs prepared in Example 1, and scanning electron microscope (b1-b3) images of WSNs@DA.

[0029] Figure 3 The formation mechanism of WSNs@DA prepared in Example 1 is driven by the Marangoni effect.

[0030] Figure 4 The images are scanning electron microscope (SEM) images of WSNs@SPMIPs prepared under different PMIPs ratios (a1-a3) and different reaction times (b1-b3) in Example 1.

[0031] Figure 5 The infrared spectra of CP, WSNs, WSNs@DA, and WSNs@SPMIPs prepared in Example 1 are shown.

[0032] Figure 6 Thermogravimetric analysis spectra of WSNs, WSNs@DA, and WSNs@SPMIPs prepared in Example 1.

[0033] Figure 7 The kinetic data and model fitting curves for the adsorption of dA by WSNs@SPMIPs and WSNs@SPNIPs prepared in Example 1 at 298 K are shown.

[0034] Figure 8 The equilibrium data and model fitting curves for the adsorption of dA by WSNs@SPMIPs and WSNs@SPNIPs prepared in Example 1 at 298 K are shown.

[0035] Figure 9 The results show the single-component adsorption of dC, dG, dA, and AMP by the WSNs@SPMIPs and WSNs@SPNIPs prepared in Example 1.

[0036] Figure 10 The results show the regeneration adsorption of WSNs@SPMIPs in Example 1. Detailed Implementation

[0037] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0038] The evaluation of the recognition performance in the specific embodiment of the present application is carried out according to the following method: 2 mL of a fixed concentration of dA solution is added to a 10 mL centrifuge tube and a certain amount of WSNs@SPMIPs adsorbent is added, and placed in a 25 o C constant temperature water area for several hours, after adsorption is completed, the adsorbent is recovered and the remaining dA solution is determined by ultraviolet visible spectrophotometer, and the adsorption capacity is calculated according to the result; 2 mL of dA solution with an initial concentration of 300 μmol / L is added to a 10 mL centrifuge tube, a certain amount of WSNs@SPMIPs adsorbent is added, and is taken out at a certain time gradient, and the adsorption capacity is calculated according to the result, which is used to participate in the study of the kinetic performance of WSNs@SPMIPs adsorbent; different gradient concentrations of dA solution are configured and a certain amount of adsorbent is added, and the adsorption capacity is calculated according to the result, which is used to participate in the study of the adsorption equilibrium performance of WSNs@SPMIPs adsorbent; finally, several nucleoside compounds with similar structure and properties, such as 2-deoxyguanosine (dG), 2-deoxycytidine (dC) and adenosine monophosphate (AMP), are selected as selective adsorbents to participate in the study of the selective recognition performance of the adsorbent.

[0039] The present application is further described below in conjunction with specific implementation examples.

[0040] Example 1

[0041] (1) Preparation of CP: 86 mg of graft monomer methacrylic acid MAA, 129 mg of functional monomer 1-(vinylbenzyl)thymine VBT, 344 mg of post-crosslinking monomer cinnamoyloxyethyl methacrylate CEMA, and 12.04 mg of photoinitiator AIBN are dissolved in THF solution, deoxygenated by nitrogen, and stirred at 65°C in an oil bath environment for 12 h. After cooling to room temperature, it is precipitated and collected with n-hexane, and vacuum dried at 50°C for 48 h to obtain the functional copolymer CP.

[0042] (2) Preparation of PMIPs: 100 mg of the previously synthesized copolymer CP (MAA-VBT-CEMA) and 10 mg of the template molecule 2'-deoxyadenosine dA are pre-assembled in a 22.5 mL DCM solution for 1.5 h, and then the complex is dispersed in a quartz reactor and subjected to photocrosslinking and solvent evaporation under ultraviolet irradiation at a wavelength of 365 nm for 12 h. After the reaction, the unreacted CP is removed by washing with DCM, and finally the template molecule is eluted with a methanol / acetic acid (9:1, v / v) solution to obtain the post-crosslinked imprinted polymer material (PMIPs).

[0043] Meanwhile, for comparison, the present application also prepared the post-crosslinked non-imprinted polymer material (PNIPs) at the same time, the synthesis steps are basically the same as above, only without adding the template molecule dA.

[0044] (3) Preparation of WSNs: Dissolve 500 mg CTAB and 400 mg n-butanol in 7.5 mL aqueous urea solution (0.4 M), add 7.5 mL cyclohexane to the uniform mixture. Under continuous mechanical stirring, add 400 mg TEOS dropwise, continue stirring at room temperature for 30 min and heat treatment at 70℃ for 20 h. The obtained product is washed with acetone and ethanol respectively, then dispersed in 20 mL ethanol, add 2.0 mL 12 M hydrochloric acid and stir vigorously at 70℃ for 12 h, and then washed with ethanol to obtain WSNs.

[0045] (4) Preparation of WSNs@DA: Disperse 50 mg WSNs in 10 mL Tris buffer solution (10 mM, adjust pH to 8.5 with KOH), and the solution contains 50 mg DA. Then, add 0.75 mL DMSO, and the interfacial water layer on the surface of WSNs is dynamically replaced by the interfacial tension gradient driven by the Marangoni effect, and then continuously stirred at room temperature for 18 h. The composite is washed with deionized water and ethanol, and finally vacuum dried to obtain DA functionalized WSNs (WSNs@DA) with uniform surface coverage.

[0046] (5) Preparation of WSNs@SPMIPs: Activate 50 mg PMIPs, 50 mg NHS and 50 mg EDC in 22.5 mL DMSO for 5 min, then add 50 mg WSNs@DA, and continuously stir the reaction at room temperature for 6 h. The obtained hybrid material is separated by centrifugation, washed with DMSO / ethanol, and vacuum dried to obtain WSNs-based surface post-crosslinked imprint adsorbent, i.e. WSNs@SPMIPs.

[0047] For comparison, the present application also prepared WSNs-based surface post-crosslinked imprint adsorbent (WSNs@SPNIPs) at the same time, the synthesis steps are the same as above, only without adding the template molecule dA during the preparation process.

[0048] Example 2

[0049] (1) Preparation of CP: A functional copolymer CP was prepared by dissolving 86 mg of grafting monomer methacrylic acid (MAA), 172 mg of functional monomer l-(vinylbenzyl)thymine (VBT), 516 mg of post-crosslinking monomer cinnamoyloxyethyl methacrylate (CEMA), and 14.62 mg of photoinitiator AIBN in THF solution, stirring for 18 h at 65 °C in an oil bath environment after nitrogen deoxygenation, precipitating and collecting after cooling to room temperature with n-hexane, and vacuum drying at 50 °C for 48 h.

[0050] (2) Preparation of PMIPs: A functional copolymer CP (MAA-VBT-CEMA) of 100 mg was pre-assembled with 13.3 mg of template molecule 2'-deoxyadenosine dA in 30 mL of DCM solution for 2 h, and then the complex was dispersed in a quartz reactor for photocrosslinking and solvent evaporation under UV irradiation at a wavelength of 254 nm for 12 h. After the reaction, unreacted CP was removed by washing with DCM, and finally the template molecules were eluted with a methanol / acetic acid (9: 1, v / v) solution to obtain the post-crosslinked imprinted polymer material (PMIPs).

[0051] (3) Preparation of WSNs: 500 mg of CTAB and 500 mg of n-butanol were dissolved in 7.5 mL of urea aqueous solution (0.4 M), and 10 mL of cyclohexane was added to the uniform mixture. 500 mg of TEOS was added dropwise under continuous mechanical stirring, and stirring was continued at room temperature for 30 min and heat treatment at 70 °C for 20 h. The resulting product was washed with acetone and ethanol, respectively, and then dispersed in 20 mL of ethanol, and 2.0 mL of 12 M hydrochloric acid was added and stirred vigorously at 70 °C for 12 h, and then washed with ethanol to obtain WSNs.

[0052] (4) Preparation of WSNs@DA: 50 mg of WSNs was dispersed in 20 mL of Tris buffer solution (10 mM, pH adjusted to 8.5 with KOH), and the solution contained 100 mg of DA. Subsequently, 1.5 mL of DMSO was added, and the interfacial water layer on the surface of the WSNs was dynamically replaced by the interfacial tension gradient driven by the Marangoni effect, and then continuously stirred at room temperature for 24 h. The composite was washed with deionized water and ethanol, and finally vacuum dried to obtain DA-functionalized WSNs (WSNs@DA) with uniform surface coverage.

[0053] (5) Preparation of WSNs@SPMIPs: The obtained hybrid material was separated by centrifugation and washed with DMSO / ethanol, and then dried under vacuum to obtain WSNs@SPMIPs.

[0054] Example 3

[0055] (1) Preparation of CP: The 86 mg of grafting monomer methacrylic acid MAA, 215 mg of functional monomer 1-(vinylbenzyl)thymine VBT, 688 mg of post-crosslinking monomer cinnamoyloxyethyl methacrylate CEMA, 17.2 mg of photoinitiator AIBN were dissolved in THF solution, and after nitrogen deoxygenation, stirring at 65°C in an oil bath environment for 24 h, cooling to room temperature, and then precipitated and collected with n-hexane, and vacuum dried at 50°C for 48 h to obtain the functional copolymer CP.

[0056] (2) Preparation of PMIPs: The 100 mg of previously synthesized copolymer CP (MAA-VBT-CEMA) and 15 mg of template molecule 2'-deoxyadenosine dA were pre-assembled in 37.5 mL of DCM solution for 2.5 h, and then the complex was dispersed in a quartz reactor and subjected to photo-crosslinking and solvent evaporation under UV irradiation at a wavelength of 254 nm for 12 h. After the reaction, unreacted CP was removed by washing with DCM, and finally the template molecule was eluted with a methanol / acetic acid (9:1, v / v) solution to obtain the post-crosslinked imprinted polymer material (PMIPs).

[0057] (3) Preparation of WSNs: 500 mg of CTAB and 600 mg of n-butanol were dissolved in 7.5 mL of urea aqueous solution (0.4 M), and 12.5 mL of cyclohexane was added to the uniform mixture. 600 mg of TEOS was added dropwise under continuous mechanical stirring, and stirring was continued at room temperature for 30 min and heat treatment at 70°C for 20 h. The obtained product was washed with acetone and ethanol, respectively, and then dispersed in 20 mL of ethanol, and 2.0 mL of 12 M hydrochloric acid was added and stirred vigorously at 70°C for 12 h, and then washed with ethanol to obtain WSNs.

[0058] (4) Preparation of WSNs@DA: 50 mg of WSNs were dispersed in 30 mL of Tris buffer solution (10 mM, pH adjusted to 8.5 with KOH), which contained 150 mg of DA. Then, 2.25 mL of DMSO was added to dynamically displace the interfacial water layer on the WSN surface via the Marangoni effect-driven interfacial tension gradient, followed by continuous stirring at room temperature for 30 h. The composite material was washed with deionized water and ethanol, and finally vacuum dried to obtain DA-functionalized WSNs with uniform surface coverage (WSNs@DA).

[0059] (5) Preparation of WSNs@SPMIPs: 150 mg PMIPs, 100 mg NHS, and 100 mg EDC were activated in 37.5 mL DMSO for 5 min, followed by the addition of 50 mg WSNs@DA. The reaction was carried out with continuous stirring at room temperature for 18 h. The hybrid material obtained by centrifugation was washed with DMSO / ethanol and then vacuum dried to obtain the WSNs-based surface post-crosslinking imprinted adsorbent, namely WSNs@SPMIPs.

[0060] Figure 1 The NMR spectrum (a) and gel permeation chromatogram (b) of the copolymer CP prepared in Example 1 demonstrate the successful preparation of the copolymer through analysis of specific functional groups and calculate the average molecular weight of the copolymer through curve fitting.

[0061] Figure 2 Scanning electron microscopy (a1) and transmission electron microscopy (a2-a3) of the original WSNs prepared in Example 1 demonstrate the successful preparation of radially distributed wrinkled silicon material WSNs.

[0062] In addition, b1-b3 are scanning electron microscope images of WSNs from Examples 1-3 after being adhered with different DA ratios (1:1, 1:2, 1:3), which proves the successful adhesion of DA and also discusses the optimal DA feed ratio.

[0063] Figure 3 The formation mechanism of WSNs@DA prepared in Example 1 is driven by the Marangoni effect. The results from AI show that appropriate solvent selection can effectively promote the diffusion of solvent on the substrate surface through the Marangoni effect at the liquid-liquid interface, thereby promoting direct contact.

[0064] Figure 4Figures a1-a3 show SEM images of WSNs@SPMIPs modified with different PMIPs ratios prepared in Examples 1-3 (1:1, 1:2, 1:3); while figures b1-b3 show SEM images of WSNs@SPMIPs prepared at different amidation grafting times (6 h, 12 h, 18 h). The optimal feed ratio and optimal reaction time of the copolymer were established through discussion of different ratios and reaction times.

[0065] Figure 5 The infrared spectra of WSNs, CP, WSNs@DA and WSNs@SPMIPs prepared in Example 1 are shown. Figure 5 This further demonstrates the successful synthesis of CP and WSNs, as well as the successful adhesion of DA to the surface of WSNs and the successful preparation of the adsorbent WSNs@SPMIPs.

[0066] Figure 6 Thermogravimetric analysis (TGA) diagrams of WSNs, WSNs@DA, and WSNs@SPMIPs prepared in Example 1 are shown. Figure 6 The mass loss at the corresponding temperature further confirms the successful preparation of SMIPs on the surface of WSNs.

[0067] Experimental Example 1: Two mg of the adsorbents WSNs@SPMIPs or WSNs@SPNIPs from Example 1 were added and dispersed in 2 mL of 2′-deoxyadenosine (dA) solution at a concentration of 300 μmol / L. Adsorption was performed at room temperature in a shaker for 15, 30, 60, 120, 180, 240, 360, and 480 min, respectively. WSNs@SPMIPs or WSNs@SPNIPs were then removed by centrifugation. The supernatant was then filtered through a Millipore nitrocellulose membrane (0.45 mm pore size) to remove suspended particles. Subsequently, the dA concentration in the filtrate was measured at 259 nm using a UV-Vis spectrophotometer, and the results were used to obtain... Figure 7 The time to adsorption equilibrium was calculated. Results showed that in the initial 180 min, the adsorption capacities of both WSNs@SPMIPs and WSNs@SPNIPs increased rapidly, with WSNs@SPMIPs exhibiting significantly higher adsorption efficiency than WSNs@SPNIPs. After adsorption equilibrium was reached, the equilibrium adsorption capacity of WSNs@SPMIPs for dA was also much larger than that of WSNs@SPNIPs. This indicates that the introduction of the post-crosslinking imprinting strategy generated more highly recognizable sites, thereby greatly improving the adsorption capacity of WSNs@SPMIPs.

[0068] Experimental Example 2: Two mg of the adsorbents WSNs@SPMIPs or WSNs@SPNIPs from Example 1 were dispersed in 2 mL of 2′-deoxyadenosine (dA) solution, with initial dA concentrations of 10, 30, 60, 100, 150, 300, 700, and 1000 μmol / L, respectively. After adsorption in a shaker at room temperature for 3 h, WSNs@SPMIPs or WSNs@SPNIPs were removed by centrifugation. The supernatant was then filtered through a Millipore nitrocellulose membrane (0.45 mm pore size) to remove suspended particles. The dA concentration in the filtrate was then measured at 259 nm using a UV-Vis spectrophotometer. The results were used to obtain... Figure 8 The adsorption capacity was calculated. The results showed that at 25°C, the maximum adsorption capacity of WSNs@SPMIPs was 93.14 μmol·g⁻¹, while the maximum adsorption capacity of the non-imprinted adsorbent WSNs@SPNIPs was only 44.70 μmol·g⁻¹. This result highlights the effectiveness of the post-crosslinking strategy in maintaining template integrity, i.e., enhancing the affinity of dA by minimizing free radical-induced side reactions and optimizing spatial thymine-adenine complementary recognition during imprinted polymerization. This further demonstrates that WSNs@SPMIPs is a highly efficient adsorbent for dA.

[0069] Experimental Example 3: Two mg of the adsorbents WSNs@SPMIPs or WSNs@SPNIPs from Example 1 were added to 2 mL of PBS solution (pH = 7.4, 50 μmol / L), which contained 300 μmol / L of 2'-deoxyguanosine dG, 2'-deoxycytidine dC, 5'-adenosine monophosphate AMP, and 2'-deoxyadenosine dA, respectively. After 3 h of adsorption, the supernatant was filtered through a Millipore nitrocellulose membrane, and the concentration of each compound in the filtrate was determined using a UV-Vis spectrophotometer at 253 nm (dG), 271 nm (dC), 260 nm (AMP), and 259 nm (dA). The results were used to derive... Figure 9 The results showed that the selective recognition order of WSNs@SPMIPs for dA and competing nucleoside analogs was dA > AMP > dG > dC. This further proves that there are imprinted recognition sites in the adsorbent WSNs@SPMIPs that are consistent with the shape and size of the template molecule dA, which makes WSNs@SPMIPs have a specific recognition effect on dA.

[0070] Experimental Example 4: Add 2.0 mg of the adsorbent WSNs@SPMIPs to a centrifuge tube, followed by 2.0 mL of dA solution with an initial concentration of 300 μmol / L. After static adsorption under water bath shaking conditions for 3 h, separate the adsorbent and solution by centrifugation and filtration. Detect unadsorbed dA molecules using UV-vis at a wavelength of 259 nm. Calculate... Q e The WSNs@SPMIP adsorbent collected after adsorption of dA was regenerated by soaking in 50 mL of methanol / acetic acid (9:1, v / v) solution to obtain regenerated WSNs@SPMIP adsorbent. This step was repeated five times, with two parallel experiments conducted. The results were then used to draw conclusions. Figure 10 The results showed that after five regeneration cycles, the adsorption capacity of WSNs@SPMIP for dA was 90.27% of that in the first cycle. The slight loss may be due to the destruction of some sites within the adsorbent folds after five regeneration cycles or the failure to completely elute some dA.

[0071] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Therefore, although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a surface post-crosslinked molecularly imprinted polymer, characterized by, The method comprises the following steps: (1) Preparation of functional copolymer CP: Dissolve grafting monomer methacrylic acid MAA, functional monomer 1-(vinylbenzyl) thymine VBT, post-crosslinking monomer cinnamoyloxyethyl methacrylate CEMA, and photoinitiator azobisisobutyronitrile AIBN in THF solution, stir under oil bath environment after nitrogen deoxygenation, precipitate and collect after cooling to room temperature, and vacuum dry to obtain MAA-VBT-CEMA, i.e. functional copolymer CP; (2) Preparation of PMIPs: Pre-assemble the functional copolymer CP prepared in step (1) and template molecule 2'-deoxyadenosine dA in dichloromethane DCM; then disperse the complex in a quartz reactor, perform photocrosslinking and solvent evaporation under ultraviolet irradiation of a certain wavelength, wash with DCM after reaction to remove unreacted CP, and finally elute the template molecule with methanol / acetic acid solution to obtain post-crosslinked molecularly imprinted polymer material PMIPs; (3) Preparation of wrinkle-structured nanosilica WSNs: Dissolve CTAB and n-butanol in urea aqueous solution, add cyclohexane to the uniform mixture, drop TEOS under continuous mechanical stirring, continue stirring at room temperature, and perform first heat treatment, wash the obtained product with acetone and ethanol respectively, disperse in ethanol, add hydrochloric acid for second heat treatment, and wash with ethanol to obtain WSNs; (4) Preparation of WSNs@DA: Disperse the WSNs prepared in step (3) in a Tris buffer solution containing a certain amount of DA; then add a certain amount of DMSO, drive the interfacial water layer on the surface of WSNs by the interfacial tension gradient dynamic displacement of the Marangoni effect, and then continuously stir for a certain time at room temperature; wash the composite material with deionized water and ethanol, and finally vacuum dry to obtain DA functionalized WSNs with uniform surface coverage, i.e. WSNs@DA; (5) Preparation of WSNs@SPMIPs: Activate PMIPs prepared in step (2), hydroxysuccinimide (NHS), and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) in DMSO, then add WSNs@DA prepared in step (4), continuously stir for a certain time at room temperature, separate the obtained hybrid material by centrifugation, wash with DMSO / ethanol, and vacuum dry to obtain WSNs-based surface post-crosslinked molecularly imprinted polymer WSNs@SPMIPs.

2. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (1), the mass ratio of MAA, VBT, CEMA and AIBN is 1 mg:(1.5-2.5) mg:(4-8) mg:(0.14-0.2) mg; the stirring time under oil bath environment is 12-24 h, and the oil bath temperature is 65℃; the vacuum drying temperature is 50℃, and the time is 48 h.

3. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (2), the mass ratio of the functional copolymer CP and the template molecule dA is 1 mg:(0.1-0.15) mg; the pre-assembly time is 1.5-2.5 h; the wavelength of the ultraviolet lamp is 254 nm-390 nm; and the reaction time under ultraviolet light is 12 h.

4. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (3), the mass ratio of CTAB, n-butanol and TEOS is 1 mg:0.8-1.2 mg:0.8-1.2 mg. The mass ratio of CTAB, urea aqueous solution and cyclohexane is 500 mg:7.5 mL:7.5-12.5 mL, wherein the concentration of the urea aqueous solution is 0.4 M.

5. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (3), the temperature of the first heat treatment is 70°C, and the time is 20 h; the temperature of the second heat treatment is 70°C, and the time is 12 h; and the concentration of the hydrochloric acid is 12 M.

6. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (4), the mass ratio of the WSNs and DA is 1 mg:(1-3) mg.

7. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (4), the mass ratio of the WSNs, the Tris buffer solution and DMSO is 50 mg:(10-30) mL:(0.75-2.25) mL; the concentration of the Tris buffer solution is 10 mM, and the pH is adjusted to 8.5 with KOH; and the stirring time is 18-30 h.

8. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (5), the mass ratio of the WSNs@DA, NHS, EDC and PMIPs is 1 mg:(1-2) mg:(1-2) mg:(1-3) mg.

9. The method for preparing the surface-crosslinked molecularly imprinted polymer as described in claim 1, characterized in that, In step (5), the activation time is 5 min, and the stirring time is 6-18 h.

10. Use of the surface post-crosslinked molecularly imprinted polymer WSNs@SPMIPs prepared by the preparation method of any one of claims 1-9 for specific adsorption and separation of dA.